Cumulative effect of yeast extract and fructooligosaccharide supplementation on composition and metabolic activity of elderly colonic microbiota in vitro. (January 2019) - Doo, Eun-Hee; Schwab, Clarissa; Chassard, Christophe; Lacroix, Christophe
Graphical abstract: Highlights: Reproducible effects of yeast extract in PolyFermS elderly colonic fermentation model. Yeast extract increases butyrate formation and the abundance of butyrate producers. Yeast extract enhances the abundance of Lactobacillaceae, and Bifidobacterium. Yeast extract and fructooligosaccharides exhibit cumulative effects on butyrate production. Abstract: Concurrent with a decline in general health, elderly gut microbiota is characterized by reduced stability compared to adults, and is impacted by living condition and diet. Dietary supplementation was suggested to stabilize and promote elderly gut microbiota. We used two PolyFermS models to investigate the impact of fructooligosaccharides (FOS), nucleosides (NS), and yeast extract (YE) supplementation on elderly colonic microbiota in vitro . NS, YE and FOS tested separately and combined at different addition levels increased the abundance of butyrate producers, lactobacilli and bifidobacteria. FOS and YE cumulatively increased butyrate levels, while propionate productions were decreased. Gene expression analysis indicated that FOS enhanced abundance of transcripts related to 'Di-and Oligosaccharides' and 'Fermentation' while treatments with FOS and YE alone and in combination altered the transcriptional profile of 'Amino Acids and Derivatives'. Our findings suggest that YE rich in nucleotides, amino acids, vitamins and minerals, enhance the butyrogenic effect of FOS.